429 HEADACHE IN SYSTEMIC LUPUS AND SYSTEMIC LUPUS ERYTHEMATOSUS DISEASE ACTIVITY. (1st January 2005) - Hansen, H.; Sibbitt, W. L.; Bankhurst, A. D.; Brandt, J.; Wong, C.; Johnson, C.
Abstract : Background: Headache (HA) is common to SLE and is a component of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), however, it precise characterization in both situations has been limited. Objective: 1) To evaluate headache characteristics unique to SLE and SLE disease activity. Methods: 436 SLE patients and 86 controls participating in the University of New Mexico Lupus Cohort were evaluated prospectively and cross-sectionally through physcial examination, neuropsych inventory and medical interview about headache characteristics. All subsets regression and multivariate modeling was used to analyze the HA characteristics associated with increased SLEDAI. Results: Patients with SLE had significantly more HA now (current HA), headache frequency, HA more frequent, N/V, photophobia, visual, activity, audio, decreased cognition, decreased performance, incapacitating HA, increased HA severity and muscle tenderness than controls. SLE had 20% more vascular-type headache than control (p=.002). Overall, SLE patients experienced 7.4 more days/month of headache than control (p≤.001). Females with SLE experienced 8.1 more days per month of headache (p≤.001) than control females. When comparing male vs female patients with SLE, females experienced significantly more frequent headaches than males with SLE (10.8 vs 5.4 days/month, respectively, p≤.001). Additionally, females experienced increased duration (6.1 vs 3.6 hours), severity (5.1 vs 3.5), more current HA, more constant HA, more n/v, photoph, tearing, visual activity, decreased activity, decreased cognition, decrease performance and more incapacitating HA. In the multivariate, paired analyses, HA frequency and duration most closely predicted total SLEDAI (r=.54, p≤.0001). Conclusions: HA in SLE is more frequent, more severe and more vascular than HA in controls. The characteristics most closely associated with increased disease activity are frequency and duration ≥ 8 days/month and ≥ 4 hours. HA should indeed be a component of SLEDAI, but should include frequency and duration, not the current definition of"Lupus Headache" which is probably incorrect. This suggests a need for reconceptualization of "Lupus Headache" and inclusion of headache in SLEDAI as outlined above.